PENINGKATAN KESADARAN DAN LITERASI HUKUM TERHADAP KEAMANAN SERTA PRIVASI DATA DAN INFORMASI - Saut Pintubipar Saragih; Mesri Silalahi; Irene Svinarky (ASOSIASI IDEBAHASA KEPRI, 2022)
Data and information security, which is currently increasingly important, has resulted in many parties making efforts to control data and information at a better level, including data and information held by students at SMK Tunas Muda Karya Batam, community service activities targeting schools. implemented will provide training and guidance to students and students in the school to improve skills in securing personal data and information so that there is no misuse to the detriment of participants in the development of laws related to information and telecommunications technology or IT will also be given to increase the awareness of students and students or all participants in using internet-based platforms. Increasing the ability of participants in the information technology aspect along with legal awareness in digital literacy brackets and legal literacy allows participants to have the ability to avoid mistakes and increase expertise in using platforms and the internet. the target of this activity is to reduce the misuse of data and information as well as law violations committed in activities related to digital platforms or the internet.